Core–Shell Nanoparticle Coating as an Interfacial Layer for Dendrite-Free Lithium Metal Anodes - Liu, Wei (ACS Cent Sci, 2017)
[Image: see text] Lithium metal based batteries represent a major challenge and opportunity in enabling a variety of devices requiring high-energy-density storage. However, dendritic lithium growth has limited the practical application of lithium metal anodes. Here we report a nanoporous, flexible and electrochemically stable coating of silica@poly(methyl methacrylate) (SiO(2)@PMMA) core–shell nanospheres as an interfacial layer on lithium metal anode. This interfacial layer is capable of inhibiting Li dendrite growth while sustaining ionic flux through it, which is attributed to the nanoscaled pores formed among the nanospheres. Enhanced Coulombic efficiencies during lithium charge/discharge cycles have been achieved at various current densities and areal capacities.